Soluble TREM-1 plasma levels are associated with acute kidney injury, acute atrial fibrillation and prolonged ICU stay after cardiac surgery- a proof-concept study - Vandestienne, Marie; Braik, Rayan; Lavillegrand, Jean-Rémi; Hariri, Geoffroy; Demailly, Zoe; Ben Hamouda, Nadine; Tamion, Fabienne; Clavier, Thomas; Ait-Oufella, Hafid (Frontiers in Cardiovascular Medicine, 2023)
Background Cardiopulmonary bypass (CPB) during cardiac surgery leads to deleterious systemic inflammation. We hypothesized that TREM-1, a myeloid receptor shed after activation, drives systemic inflammation during CPB. Methods Prospective observational bi-centric study. Blood analysis (flow cytometry and ELISA) before and at H2 and H24 after CPB. Inclusion of adult patients who underwent elective cardiac surgery with CPB. Results TREM-1 expression on neutrophils decreased between H0 and H2 while soluble (s)TREM-1 plasma levels increased. sTREM-1 levels increased at H2 and at H24 (p < 0.001). IL-6, IL-8, G-CSF and TNF-α, but not IL-1β, significantly increased at H2 compared to H0 (p < 0.001), but dropped at H24. Principal component analysis showed a close relationship between sTREM-1 and IL-8. Three patterns of patients were identified: Profile 1 with high baseline sTREM-1 levels and high increase and profile 2/3 with low/moderate baseline sTREM-1 levels and no/moderate increase overtime. Profile 1 patients developed more severe organ failure after CPB, with higher norepinephrine dose, higher SOFA score and more frequently acute kidney injury at both H24 and H48. Acute atrial fibrillation was also more frequent in profile 1 patients at H24 (80% vs. 19.4%, p = 0.001). After adjustment on age and duration of CPB, H0, H2 and H24 sTREM-1 levels remained associated with prolonged ICU and hospital length of stay. Conclusions Baseline sTREM-1 levels as well as early kinetics after cardiac surgery identified patients at high risk of post-operative complications and prolonged length of stay.